Occupational exposure to power frequency magnetic fields and risk of non-Hodgkin lymphoma. Issue 1 (21st March 2006) - Karipidis, K; Benke, G; Sim, M; Fritschi, L; Yost, M; Armstrong, B; Hughes, A M; Grulich, A; Vajdic, C M; Kaldor, J; Kricker, A
Abstract : Objectives: To investigate the risk of non-Hodgkin lymphoma (NHL) using a job-exposure matrix (JEM) to assess exposure to occupational magnetic fields at the power frequencies of 50/60 Hz. Methods: The study population consisted of 694 cases of NHL, first diagnosed between 1 January 2000 and 31 August 2001, and 694 controls from two regions in Australia, matched by age, sex and region of residence. A detailed occupational history was given by each subject. Exposure to power frequency magnetic fields was estimated using a population-based JEM which was specifically developed in the United States to assess occupational magnetic field exposure. The cumulative exposure distribution was divided into quartiles and adjusted odds ratios were calculated using the lowest quartile as the referent group. Results: For the total work history, the odds ratio (OR) for workers in the upper quartile of exposure was 1.48 (95% CI 1.02 to 2.16) compared to the referent (p value for trend was 0.006). When the exposure was lagged by 5 years the OR was 1.59 (95% CI 1.07 to 2.36) (p value for trend was 0.003). Adjusting for other occupational exposures did not significantly alter the results. Conclusions: These findings provide weak support for the hypothesis that occupational exposure to 50/60 Hz magnetic fields increases the risk of NHL.